Changing Earth Sciences - Keen, M. (Geoscience Canada, 1989)
Summary Canada's economic dependence on naturalresources has declined — minerals, oil and gas, forestry, trapping, fishing and agriculture contribute proportionately much less to the Gross Domestic Product than they did 30 years ago. Advanced materials, advanced crops and service industries appear to be replacing our traditional bases.